(untitled) (Journal of Educational Sciences, 2021)
This article discusses the specifics of distance learning using a synergetic approach to education. Because today, one of the new areas that are closely related to the goals of methodological, pedagogi- cal, didactic training and developmental education is synergetics. Synergetics performs a key function in ensuring the development and promotion of the entire human being as an intellectual and biological ob- ject. This indicates that it is at the forefront compared to other industries, synergetics performs and imple- ments human behavior and its tracking and targeted activities. This function of synergetics-in the process of learning, it reveals parallels between different phenomena. Working remotely using a synergistic ap- proach, groups of teachers use various online platforms for asynchronous, synchronous communication. Google Docs and spreadsheets, open for sharing in group work, are very convenient. They allow you to work at the same time, write reviews of works and improve. Thanks to this, teachers support each other and gain experience in distance learning and learning. The joint activity of teachers in the planning and control of lessons will contribute to the selection and dissemination of effective pedagogical practices for distance learning using a synergistic methodology. Key words: synergetics, distance learning, Case technology, asynchronous, Synchronous learning.